Coupling effect of strain rate and specimen size on the compressive properties of coral aggregate concrete: A 3D mesoscopic study. (1st November 2020) - Wu, Zhangyu; Zhang, Jinhua; Yu, Hongfa; Ma, Haiyan; Chen, Li; Dong, Wen; Huan, Yi; Zhang, Yadong
Abstract: The dynamic compressive behavior of concrete is closely associated with the specimen size effect and the coupling effect of strain rate and specimen size on the compressive properties is something there worthy studying for the development and application of coral aggregate concrete (CAC). A novel 3D mesoscale modelling approach taking the random characteristics of aggregates is developed for the numerical study in the present work. The specimen diameter of numerical cylinder with the slenderness of 1/2 varies from 50 mm to 200 mm, and the strain rate is within the range of 10 −3 –200s −1 . Employing the 3D mesoscale model, the dynamic compressive responses of CAC, i.e., stress-strain relation, failure pattern and process, energy evolution process, etc. have been simulated and analyzed systematically. Both the effect of strain rate and specimen size have been qualitatively and quantitatively discussed. Through the comparison of numerical and existing test data, it is verified that the compressive behaviors of CAC under different conditions could be characterized and predicted using the 3D mesoscale model. In addition, all above-listed properties are related to the strain rate and specimen size at different degrees. The strain rate effect law on the CAC's strength and absorbed energy can be well expressed using a quadratic function and an exponential function, respectively. And the relationship between strength and specimen size can be mathematically formulated by a power function. Furthermore, a coupling effect law of strain rate and specimen size on the strength of CAC has been proposed and validated based on numerical and test data, which is meaningful for the properties prediction of CAC. Graphical abstract: Image 1